Environmental education in settlement projects in the Amazon Agroextractivist Tocantina, Para - Brazil - Gonçalves, Denival de Lira; Brasil, Davi do Socorro Barros (Revista Hipótese, 2017)
This study research about the perception and the importance of environmental education as an essential space of construct a sustainability perspective in Agroextractive Settlement Projects – PAE’S in the Amazon Tocantina, which comprises the region of Lower Tocantins, in the state of Pará, more especific, the Settlement Project Agroextrativista Island Cacoal, in Cametá district - State of Pará. Were interviewed 253 families originally owned by the Community of Cacoal, using semi-structured questionnaires.